Integrating SOLE–TASC to Enhance Students’ Collaborative and Communicative Competencies in Science Learning - Zahwa, Aisha Innayatul; Amelia, Rizki Nor; Astuti, Sri Rejeki Dwi; Fitriani, Ika Nur (JURNAL EKSAKTA PENDIDIKAN (JEP), 2025)
Collaboration and communication are essential 21st-century skills. Observations and interviews suggest that these are among students in science learning are still not fully developed. This study aims to analyze the differences in collaboration and communication skills between the experimental and control classes and examine the relationship between these two skills through implementation of the Self-Organized Learning Environment (SOLE) model, integrating thinking actively in a social context (TASC). The research employed a quantitative method with a quasi-experimental design. The study groups being a pretest–posttest control group involving two seventh-grade classes (VII G and VII H), selected through cluster random sampling. Research instruments included validation sheets, questionnaires, and observation rubrics. The data analysis techniques employed included the homogeneity test, the normality test, the independent sample t-test, and the correlation test. The findings revealed significant improvements in collaboration and communication skills in the experimental class compared to the control class (p < .05). Pearson correlation analysis further indicated a very strong positive relationship (r = .854; p < .05) between the two skills in the experimental class. These results suggest that integrating the SOLE-TASC is effective in enhancing students’ collaboration and communication skills in science learning compared to conventional instruction.